IMPROVEMENT OF IMMUNOGENETIC CHARACTERISTICS AND PREVENTION OF JUVENILE IDIOPATHIC ARTHRITIS IN CHILDREN OF FERGANA VALLEY - Mullajonov Khasanboy Ergashevich (Scholar Express Journal, 2023)
Juvenile idiopathic (rheumatoid) arthritis (JIA) is a chronic, severe, progressive disease of children and adolescents, with unclear etiology and complex autoimmune pathogenesis, which is manifested by gradual destruction of joints, disrupts the growth and development of the child. , is considered a disease that negatively affects the quality of life[1]. The exact causes of this disease are unknown
Keywords: Development; infections; arthritis; immunity